The Influence of Advertising Creativity, Credibility, Lack of Irritation, Informativeness, And Entertainment on Consumer Attitudes Towards Brand on Gojek Advertising - R.A Adenia Kumala Adzani; Premananto, Gancar Candra (Southeast Asian Business Review, 2023)
This study examines the role of advertising creativity, credibility, lack of irritation, informativeness, and entertainment on consumer attitude toward the brand on Gojek X Ariel NOAH #CepetanGoSendInstant on YouTube. This research was conducted using a quantitative approach with a survey method. The data was obtained through an online survey using Google Forms to 256 respondents who are YouTube social media users in Indonesia with a minimum age of 18 years and have seen Gojek advertisement "#CepetanGoSendInstant by Ariel NOAH x GoSend" on YouTube. This research uses Structural Equation Model (SEM) analysis technique with Partial Least Square (PLS) approach. Measured variables are advertising creativity (24 indicators), credibility (3 indicators), lack of irritation (3 indicators), informativeness (2 indicators), entertainment (3 indicators), attitude toward the advertisement (3 indicators), and attitude toward the brand (3 indicators). The results showed that advertising creativity and entertainment had a significant effect on attitude toward the advertisement, while credibility, lack of irritation, and informativeness had no significant effect on attitude toward the advertisement. The results of the study also found that the attitude toward the advertisement had a significant effect on the attitude toward the brand.